2022
DOI: 10.21273/horttech04965-21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substrate Stratification on Growth of Common Nursery Weed Species and Container-grown Ornamental Species

Abstract: Substrate stratification is a method of filling nursery containers with “layers” of different substrates, or different textures of the same substrate. Recently, it has been proposed as a means to improve drainage, substrate moisture dynamics, and optimize nutrient use efficiency. Substrates layered with larger particle bark as the top portion and smaller particle bark as the bottom portion of the container profile would theoretically result in a substrate that dries quickly on the surface, thereby reducing wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…Thus, we are encouraging water retention and distribution to be more uniform throughout the container profile (i.e., promoting water retention in dryer regions and promoting drainage in wetter regions), while maintaining a similar overall porosity. Substrate stratification has also been shown to reduce weed germination (Khamare et al, 2022); however, this strategy involves layering coarse particles on top of finer particles. Thus, the upper portion of the container would dry quickly, inhibiting germination.…”
mentioning
confidence: 99%
“…Thus, we are encouraging water retention and distribution to be more uniform throughout the container profile (i.e., promoting water retention in dryer regions and promoting drainage in wetter regions), while maintaining a similar overall porosity. Substrate stratification has also been shown to reduce weed germination (Khamare et al, 2022); however, this strategy involves layering coarse particles on top of finer particles. Thus, the upper portion of the container would dry quickly, inhibiting germination.…”
mentioning
confidence: 99%
“…Results of our previous study revealed that substrate stratification reduced the growth of bittercress (Cardamine flexuosa) by 80% to 97%, and liverwort (Marchantia polymorpha) coverage was reduced by 95% to 99%. Additionally, there was no difference in the growth of ligustrum (Ligustrum japonicum) and blue plumbago (Plumbago auriculata) in stratified substrates compared with industry-standard substrates (Khamare et al, 2022). Substrate stratification with larger coarse particles as the top strata provides a mulch-like layer that holds less moisture and has no nutrient available for weed seeds to germinate and establish.…”
mentioning
confidence: 99%
“…An additional cultural or nonchemical method that could have potential as a weed management tool is "layering" or stratified substrates (Khamare et al, 2022). This is a new area of research in which multiple substrates, or the same substrate with differing physical properties, are layered within a container to accomplish a production goal, such as decreasing water use or nutrient leaching, or potentially reducing weed growth (Criscione et al, 2022;Fields et al, 2021;Khamare et al, 2022).…”
mentioning
confidence: 99%
See 2 more Smart Citations